Communities of practice in the digital age: Managing communities with the use of social networking tools - Pleshakova, Violetta (Proceedings of the International Conference on Networked Learning, 2012)
The context of the digital age, described as "information society", "network society", and "networked information economy", is highly dynamic and thought-provoking. Research efforts (Leadbeater 2008, Shirky 2008) reveal that information or knowledge society gives rise to social collaboration and fosters outburst of community formation, especially with the help of the Web 2.0 tools. These tools, in particular social networking, facilitate knowledge sharing, stimulate information exchange, and foster cross-cultural connections. What becomes possible for communities of practice when they operate online, via social networking sites like Facebook? Do particular communities on Facebook display the characteristics of dispersed, or virtual, communities of practice? This research seeks to conduct a case study of a virtual community of practice (VCoP) on Facebook and explore how this community setup contributes to knowledge sharing and creation of alternative learning paradigms. The exploratory case study focusses on Consciousness Coaching® Academy (CCA) - an international organization that offers professional coach training curriculum. Nine months of participant observation and semi-structured interviews with VCoP members reveal that community members acknowledge the existence of a CCA community, online as well as offline. Community members testify that they participate online and believe that virtual community will continue its operation in the future. With over 300 members (as of January 2012) - trainers, practicing coaches, and CCA students - this community is not only dispersed geographically, but also shows high levels of socio-cultural heterogeneity. Participant observation reveals that the VCoP is active, with an average of 32 Facebook posts per week. Community members negotiate community content and rules, respond to each other, build relationships, do things together both online and offline (for example, informal face-to-face meetups and coaching practice sessions), and share a repertoire of stories, actions, artefacts, events, concepts, tools, and discourses. The facts above attest that the Facebook group in question displays the traits of a community of practice, as defined by Wenger (1998). The case study will be nearing completion by the time of the conference (April 2012), therefore, a more accurate picture of the VCoP will be obtained, lessons learned will be derived, and recommendations for community development will be formulated.